2019
DOI: 10.3390/ijms20030547
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Protein Profiling and Biochemical Analysis of Two Contrasting Rice Genotypes Revealed Their Differential Responses to Salt Stress

Abstract: Salt stress is one of the key abiotic stresses causing huge productivity losses in rice. In addition, the differential sensitivity to salinity of different rice genotypes during different growth stages is a major issue in mitigating salt stress in rice. Further, information on quantitative proteomics in rice addressing such an issue is scarce. In the present study, an isobaric tags for relative and absolute quantitation (iTRAQ)-based comparative protein quantification was carried out to investigate the salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…This indicated that maize enhanced salt tolerance by increasing POD content. In addition, many proteomic studies have confirmed that redox related proteins are involved in salt stress in plants, including rice [42], maize [43], barley [44] and Sugar Beet ( Beta vulgaris L.) [45]. In general, oxidation and reduction reactions may improve the salt tolerance of maize.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that maize enhanced salt tolerance by increasing POD content. In addition, many proteomic studies have confirmed that redox related proteins are involved in salt stress in plants, including rice [42], maize [43], barley [44] and Sugar Beet ( Beta vulgaris L.) [45]. In general, oxidation and reduction reactions may improve the salt tolerance of maize.…”
Section: Discussionmentioning
confidence: 99%
“…The isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomic technique was used to identify the differentially-expressed proteins in leaves of two rice genotypes that differ in their tolerance to salt stress [27]. The iTRAQ protein profiling identified in both rice genotypes revealed that the differentially-expressed proteins were mainly involved in the regulation of salt-stress responses, in oxidation-reduction responses, in photosynthesis, and in carbohydrate metabolism.…”
Section: Proteomic Approachmentioning
confidence: 99%
“…The iTRAQ protein profiling identified in both rice genotypes revealed that the differentially-expressed proteins were mainly involved in the regulation of salt-stress responses, in oxidation-reduction responses, in photosynthesis, and in carbohydrate metabolism. Regarding their subcellular localization, most of them were predicted to localize in cytoplasm and chloroplasts (67.2% of the total up-regulated proteins) [27].…”
Section: Proteomic Approachmentioning
confidence: 99%
“…Consistently, the overexpression of another IRL gene, Os01g0106400, confers tolerance to ROS, which probably prevents an over production of ROS in rice cells [112]. Interestingly, Os01g0106300 is differentially expressed under salt stress in contrasting rice genotypes [33].…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in RNA sequencing techniques have provided highly efficient and relatively low-cost methods to analyse whole transcriptomes, allowing for a full characterization of the transcriptomic response of organisms to external stimuli. These new technologies have been used in several studies to characterize the genetic background of stress-tolerant rice varieties, while comparing the transcriptomic response of tolerant and sensitive genotypes to single stresses, in particular cold [5,25,26,27], drought [28,29,30,31], and salt stress [32,33,34,35,36]. These analyses allowed for the identification of genes and pathways that play major roles in conferring tolerance to single environmental cues.…”
Section: Introductionmentioning
confidence: 99%